2020
DOI: 10.3847/1538-4357/abb13b
|View full text |Cite
|
Sign up to set email alerts
|

ZTF Early Observations of Type Ia Supernovae. II. First Light, the Initial Rise, and Time to Reach Maximum Brightness

Abstract: While it is clear that Type Ia supernovae (SNe) are the result of thermonuclear explosions in C/O white dwarfs (WDs), a great deal remains uncertain about the binary companion that facilitates the explosive disruption of the WD. Here, we present a comprehensive analysis of a large, unique data set of 127 SNe Ia with exquisite coverage by the Zwicky Transient Facility (ZTF). High-cadence (six observations per night) ZTF observations allow us to measure the SN rise time and examine its initial evolution. We deve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
83
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 54 publications
(100 citation statements)
references
References 99 publications
16
83
1
Order By: Relevance
“…The high-cadence surv e y, in the first year of operations, observed a total of ∼2500 deg 2 with three visits per night in the g and r bands, aimed at finding SNe in their infancy. This surv e y has been critical for early disco v eries of SNe Ia (Yao et al 2019 ), to characterize their rise times (Miller et al 2020 ) and use the early colours as a test for explosion models and multiple populations (Bulla et al 2020 ). The surv e y also pro vides densely sampled light curves in the g and r bands for the sample presented here.…”
Section: The Partnership Sur V Eymentioning
confidence: 99%
See 1 more Smart Citation
“…The high-cadence surv e y, in the first year of operations, observed a total of ∼2500 deg 2 with three visits per night in the g and r bands, aimed at finding SNe in their infancy. This surv e y has been critical for early disco v eries of SNe Ia (Yao et al 2019 ), to characterize their rise times (Miller et al 2020 ) and use the early colours as a test for explosion models and multiple populations (Bulla et al 2020 ). The surv e y also pro vides densely sampled light curves in the g and r bands for the sample presented here.…”
Section: The Partnership Sur V Eymentioning
confidence: 99%
“…Since it has been shown that for a given decline rate, the rise times vary significantly (Ganeshalingam, Li & Filippenko 2011 ;Firth et al 2015 ;Miller et al 2020 ), we expect to gain in the precision of the distance measurement by using information in rising part of the light curve. It has been shown that this method of two light-curve widths instead of one yields a smaller scatter than if only using a single lightcurve width (Hayden, Rubin & Strovink 2019 ).…”
Section: Light-cur V E Fittingmentioning
confidence: 99%
“…Rise time data for Type II SNe are based on samples from PTF 114 and ZTF 71 . Data for SNe Ia are from the ZTF sample: peak magnitudes 115 and rise times 116 . Data for SNe Ic are taken from the PTF samples of normal 117 and broad-line 118 events.…”
Section: X-ray Observationsmentioning
confidence: 99%
“…In this exercise, we also used the LC fit with the analytical function to characterize the rise and decline parameters (again following the study of Taddia et al 2015). In order to estimate the actual rise time with respect to an estimated time of explosion (first light), we followed the methodology employed by Miller et al (2020) using both the pre-explosion upper limits and the rising part of the LC. Comparing the τ fall vs. τ rise distributions with those of the SDSS sample (Taddia et al 2015) and, in particular, investigating the rise-time distribution, we decided to remove objects with τ rise > 8 days.…”
Section: Light Curve Propertiesmentioning
confidence: 99%